The Effect of Using Colored Sand Media on the Cognitive Abilities of Children Aged 5–6 Years at TK Negeri Pembina 1 Bengkulu City - Iga Purnamasari; Evi Selva Nirwa; Masrifa Hindayani (International Journal of Education, Information Technology, and Others, 2026)
Early childhood education plays a crucial role in supporting children's growth and development, particularly in the cognitive domain. Cognitive development enables children to think, explore, solve problems, recognize concepts, and understand their surrounding environment. However, many children still experience difficulties in cognitive activities such as recognizing colors, classifying objects, understanding simple concepts, and solving basic problems. One of the learning media that can stimulate children's cognitive development is colored sand media, which provides direct sensory experiences through exploration, manipulation, and creative play activities. This study aims to determine the effect of using colored sand media on the cognitive abilities of children aged 5–6 years at TK Negeri Pembina 1 Bengkulu City. This study employed a quantitative approach using a quasi-experimental design. The participants were children aged 5–6 years enrolled at TK Negeri Pembina 1 Bengkulu City. Data were collected through observation, assessment sheets, and documentation. The collected data were analyzed using statistical techniques to compare children's cognitive abilities before and after the implementation of colored sand media in learning activities. The findings indicate that the use of colored sand media has a positive effect on children's cognitive abilities. Through activities involving colored sand, children demonstrated improvements in recognizing colors, classifying objects, understanding simple concepts, exploring their environment, and solving problems during learning activities. The hands-on and sensory-based experiences provided by colored sand media increased children's engagement, concentration, creativity, and active participation in the learning process. Therefore, the use of colored sand media can be considered an effective learning medium for enhancing the cognitive abilities of children aged 5–6 years. The implementation of attractive and interactive learning media is essential in supporting optimal cognitive development and creating meaningful learning experiences in early childhood education